Non-classical Natural Killer T Cells Modulate Plasmid DNA Vaccine Antigen Expression and Vaccine-elicited Immune Responses by MCP-1 Secretion after Interaction with a β2-Microglobulin-independent CD1d - Geiben-Lynn, Ralf (American Society for Biochemistry and Molecular Biology, 2009)
The magnitude and durability of a plasmid DNA vaccine-induced immune response is shaped by immune effector molecules at the site of vaccination. In the present study, we show that antigen expression is modified by type II NKT cells, after interaction with a β2-microglobulin-independent CD1d receptor. After activation, during the first days following plasmid DNA vaccination, NKT cells release IL-5 and MCP-1, leading to a T helper 0 (T(H)0) cytokine/chemokine profile and a stronger CD8(+)/CD4(+) T cell immune response. Our data indicate that this phenomenon was induced through the strong T(H)1 chemokine MCP-1 during the early phases of plasmid DNA vaccination because injecting the type II NKT cell-associated MCP-1 during the first 5 days led to 2–3-fold increases in vaccine-elicited T cell responses. This study demonstrates a critical role for NKT cells in plasmid DNA vaccine-induced immune responses. Manipulation of NKT cell function or co-administration of MCP-1 may represent novel methods for enhancing immune responses to plasmid DNA vaccines.